Eksistensi Living Law sebagai Perwujudan Masyarakat Adat dalam Pembaruan Sistem Hukum Pidana Nasional - Jufianty Trisna Putri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to analyze the existence of living law as a manifestation of indigenous peoples in the renewal of the national criminal law system. This research was conducted using descriptive analytical normative legal research, using secondary data obtained from literature studies as the main data and using primary data, namely related legislation as supporting data, research data collection techniques using library research, and data analysis using qualitative juridical data analysis. Based on the research results, it shows that the inclusion of living law elements in the RKUHP is a new hope in the Indonesian criminal law system which is expected to create conscious legal compliance in the community. The application of living law in the Indonesian national criminal law system can also be categorized as a progressive step in the renewal of the national criminal law system. By adopting living law in the RKUHP, the true development of national criminal law does not only mean to improve the positive legal system, but also to serve the needs of society and legal modernization. There is a difference in the understanding of the principle of legality between the KUHP and the RKUHP. The element of living law adopted in the RKUHP is a recognition of the law that lives in the community. In its application, based on the explanation in the RKUHP, living law can be an exception to the applicability of the principle of legality in criminal justice practice in Indonesia as long as it does not conflict with the principles of Pancasila, human rights, and general legal principles that apply in the community.